2016
DOI: 10.1155/2016/2513275
|View full text |Cite
|
Sign up to set email alerts
|

Macerals of Shengli Lignite in Inner Mongolia of China and Their Combustion Reactivity

Abstract: The macerals, including fusinitic coal containing 72.20% inertinite and xyloid coal containing 91.43% huminite, were separated from Shengli lignite using an optical microscope, and their combustion reactivity was examined by thermogravimetric analysis. Several combustion parameters, including ignition and burnout indices, were analyzed, and the combustion kinetics of the samples were calculated by regression. Fusinitic coal presented a porous structure, while xyloid coal presented a compact structure. The spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The role of the petrographic composition in the integrated gasification combined cycle (IGCC) was discussed by Ozer et al (2017), who studied its effect on the reactivity. Teng et al (2016) investigated the reactivity of inertinite and xyloid coal in the combustion process. They suggested that the activation energy of xyloid coal is less than that of fusinitic coal.…”
Section: Introductionmentioning
confidence: 99%
“…The role of the petrographic composition in the integrated gasification combined cycle (IGCC) was discussed by Ozer et al (2017), who studied its effect on the reactivity. Teng et al (2016) investigated the reactivity of inertinite and xyloid coal in the combustion process. They suggested that the activation energy of xyloid coal is less than that of fusinitic coal.…”
Section: Introductionmentioning
confidence: 99%
“…The statistics show that the gross reserves of global coal are about 10, 7539 trillion tons, and one of lignite is 2, 6229 trillion tons. [1] China is the world's third largest coal reserves and is the world's first coal producer (47.5%). We already know that coal reserves accounted for 13.3% of the world's total recoverable coal.…”
mentioning
confidence: 99%